Ontogeny of the Immune Response in the Ovine Lung - Sow, Fatoumata B. (2011)
Perinatal lambs are increasingly appreciated as a model to study respiratory infections of premature and newborn human infants. To explore the relationship between developmental age and immunological competence in the respiratory tract, the basal levels of expression of genes involved in innate and adaptive immune functions in the lung were examined in pre-term lambs (115 days and 130 days), at birth (145 days) and post-partum (15 days and 3 years old). Our results show that innate immune genes (TLRs-3, -4, -7, -8; SP-A, SP-D, and SBD1) were differentially expressed through development; cytokines (IFN-γ, IL-6, TNF-α) and chemokines (IL-8, MCP-1) were low during gestation and post-partum but maximal at birth; genes involved in adaptive immunity (PD-1, PD-L1, TGF-β) were present in pre-term and newborn lung, but were lower in adult lung. The results suggest that pre-term and neonatal lambs may be able to mount an immune response following infection, but that the response may not be optimal. Our studies provide an important set of comparative data on the ontogeny of lung immunity in sheep and set a framework for studies on age-dependent susceptibility to respiratory pathogens.